2010
DOI: 10.1080/14697680903358222
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate models for operational risk

Abstract: Bocker and Kluppelberg [Risk Mag., 2005, December, 90-93] presented a simple approximation of OpVaR of a single operational risk cell. The present paper derives approximations of similar quality and simplicity for the multivariate problem. Our approach is based on the modelling of the dependence structure of different cells via the new concept of a Levy copula.Dependence model, Levy copula, Multivariate dependence, Multivariate Levy process, Operational risk, Pareto distribution, Regular variation, Subexponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 9 publications
4
56
0
Order By: Relevance
“…Böcker and Klüppelberg (2010), Chavez-Demoulin et al (2006, Moscadelli (2004), Puccetti and Rüschendorf (2014), and Tursunalieva and Silvapulle (2014). All these contributions seem to agree on the use of extreme value theory, and in particular of the Generalized Pareto approximation of the right tail Ferreira 2006, Falk et al 2004), to study the behavior of large operational losses (see Subsection 2.2 for more details.).…”
Section: Introductionmentioning
confidence: 97%
“…Böcker and Klüppelberg (2010), Chavez-Demoulin et al (2006, Moscadelli (2004), Puccetti and Rüschendorf (2014), and Tursunalieva and Silvapulle (2014). All these contributions seem to agree on the use of extreme value theory, and in particular of the Generalized Pareto approximation of the right tail Ferreira 2006, Falk et al 2004), to study the behavior of large operational losses (see Subsection 2.2 for more details.).…”
Section: Introductionmentioning
confidence: 97%
“…Here we examine the LCR treaty: having set a fixed follow-up time t, we delete from the process the largest claim occurring up to and including that time. Defined in this way, the scheme incorporates a retrospective feature akin to the construction of a "lookback" option as understood in finance 1 .…”
Section: Reinsurance Modelsmentioning
confidence: 99%
“…In general, the ruin time with reinsurance will exceed or equal that without, for each sample path, and the question we address here is how to measure this effect with regard to the company's viability. 1 The LCR procedure can be made prospective by implementing it as a forward looking dynamic procedure in real time, from the cedant's point of view. Designate as time zero the time at which the reinsurance is taken out.…”
Section: Reinsurance Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the standard division of banks' activities into business lines, as required by the so-called standardized and advanced measurement approaches (BCBS 2011b, Moscadelli 2004 has even shown that for corporate finance, trading and sales and payment and settlement, the loss distribution has a deal with its extremely heavy-tailed behaviour, e.g. Böcker and Klüppelberg (2010), Chavez-Demoulin et al (2006), Chavez-Demoulin et al (2015), Moscadelli (2004), Puccetti and Rüschendorf (2014), and Tursunalieva and Silvapulle (2014). All these contributions seem to agree on the use of extreme value theory, and in particular of the Generalized Pareto approximation of the right tail (Falk et al 2004, de Haan andFerreira 2006), to study the behaviour of large operational losses (see section 2.2 for more details.).…”
Section: Introductionmentioning
confidence: 99%